Clinical characteristics and the role of IL-6 in acute-on-chronic liver failure patients with or without COVID-19: a multicenter paired cohort study - Ruoyu Yao; Guofen Xu; Xiujuan Fu; Wenrui Zhang; Han Wang; Yu Chen; Jia Yao (Frontiers in Cellular and Infection Microbiology)
Background and AimsThe impact of coronavirus disease 2019 (COVID-19) on patients with acute-on-chronic liver failure (ACLF) remains unclear. To investigate the clinical characteristics of patients with ACLF complicated with COVID-19 in order to provide evidence for the precise treatment of this patient population.MethodsA total of 34 ACLF patients with COVID-19 admitted to these three hospitals from December 2022 to August 2023 were included as the ACLF+COVID-19 group. Additionally, 34 age-, gender-, etiology-, and Model for End-Stage Liver Disease-Sodium (MELD-Na) score-matched ACLF patients were screened from 286 ACLF patients as the ACLF group. From 382 COVID-19 patients, 34 were selected as the COVID-19 group, matching the ACLF+COVID-19 group in age, gender, and illness severity. Clinical features of these three groups were compared, with the primary measure being the 28-day mortality rate in the ACLF patients and the secondary measures including clinical symptoms, laboratory tests, comorbidities, and complications in three groups.ResultsCompared with the ACLF group, the ACLF+COVID-19 group had significantly higher incidence rates of fever, cough, sputum production, fatigue, and hypoxemia (all p<0.01). Patients in the ACLF+COVID-19 group were more likely to have hepatic encephalopathy (p=0.015), lower platelet count (p=0.016) and elevated IL-6 level (p=0.026), and higher MELD-Na score (p=0.041) one week after admission, but without a significant increase in 28-day mortality rate (p=0.16).ConclusionsACLF patients with COVID-19 have increased risk for thrombocytopenia, more obvious inflammatory response, and rapid disease progression 1 week after admission, but the 28-day mortality rate is similar to that of ACLF patients without COVID-19.